Relationship between trunk diameter fluctuations and physiological variables in adult cocoa trees - Freire, Fausto; Carrillo, Manuel; Lahuathe, Braulio; Vera, Luis; Chipantiza, Alvaro; Durango, Wuellins; Rivadeneira, Betty; Garcia-Orellana, Yelitza (Frontiers in Agronomy, 2025)
It is important to know the water status of cocoa plants because a water deficit negatively affects fruit set and fruit maturity reducing their quality. The objective of this work is determining the existence of a relationship between the fluctuation of trunk diameter and the water status of adult cocoa trees which will allow a continuous and low-cost measurement of the water status of the plants. To meet this objective a trial was carried out at Hacienda La Clemencia located in the province of Guayas- Ecuador, the foliar and stem water potentials, maximum daily trunk fluctuations (MCDT), gas exchange, and soil moisture levels were evaluated. The trial was conducted for 128 days, from July to October 2023. The physiological variables were measured twice a week, while the meteorological variables, soil moisture, and MCDT were recorded continuously. The results showed that there is a correlation between the physiological variables evaluated and MCDT. In conclusion, there is a significant relationship between stem potential and MCDT in adult cocoa plants.